2022
DOI: 10.1021/acsami.2c15955
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Vacancies at the 2D Nanocrystals for Robust Bifunctional Electrocatalysts

Abstract: Hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) through water decomposition are feasible methods to produce green and clean energy. Herein, we report a facile two-step strategy for the preparation of non-noble metal defect-rich nanosheets by an electrochemical process at room temperature. First-principle calculations are used to study the bifunctional catalytic reaction mechanism of defect engineering in transition-metal dichalcogenides (TMDs); from the first-principle calculations, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…After the S vacancies were induced, the Nb 4+ peaks moved back toward higher binding energies (203.18 and 206.08 eV) in Cu 0.4 NbS 2− δ . 44 For S 2p spectra in Fig. 2b, the S 2p 3/2 and 2p 1/2 peaks shifted to higher binding energies after Cu intercalation (from 161.08 and 162.28 eV in NbS 2 to 161.88 and 160.68 eV in Cu 0.4 NbS 2 ), and they further moved to a higher range in Cu 0.4 NbS 2− δ (161.28 and 162.58 eV) after the partial removal of S atoms, implying the re-distribution of electrons after the chemical intercalation and defects induced in this system.…”
Section: Resultsmentioning
confidence: 99%
“…After the S vacancies were induced, the Nb 4+ peaks moved back toward higher binding energies (203.18 and 206.08 eV) in Cu 0.4 NbS 2− δ . 44 For S 2p spectra in Fig. 2b, the S 2p 3/2 and 2p 1/2 peaks shifted to higher binding energies after Cu intercalation (from 161.08 and 162.28 eV in NbS 2 to 161.88 and 160.68 eV in Cu 0.4 NbS 2 ), and they further moved to a higher range in Cu 0.4 NbS 2− δ (161.28 and 162.58 eV) after the partial removal of S atoms, implying the re-distribution of electrons after the chemical intercalation and defects induced in this system.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations demonstrated that the S vacancies in TaS x NSs could facilitate the electron transfer between H and TaS x , thus lowering the overpotential and promoting hydrogen generation. 102…”
Section: Modulation Strategies For Improving Her Catalytic Performancementioning
confidence: 99%